2016
DOI: 10.3892/ol.2016.4994
|View full text |Cite
|
Sign up to set email alerts
|

A sesquiterpene lactone from Siegesbeckia glabrescens suppresses Hedgehog/Gli-mediated transcription in pancreatic cancer cells

Abstract: Abstract. Pancreatic cancer is aggressive and therefore difficult to treat; however, continued efforts have been made with the aim of developing an effective therapy against the disease. The Hedgehog (Hh) signaling pathway is reportedly involved in the proliferation and survival of pancreatic cancer cells. The transcription factor glioma-associated oncogene (Gli) is a key component of the Hh signaling pathway and the primary effector of pancreatic cancer development. Inhibiting Gli is a proven therapeutic stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The dysregulated activation of the Shh signaling pathway in cancer cells is associated with tumor occurrence, drug resistance and poor cancer prognosis (18). Gli1 activates the target genes downstream of the Shh pathway (19,20). It has been reported that Rab23 is associated with the Shh signaling pathway, but whether this correlation is positive or negative is still under debate.…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulated activation of the Shh signaling pathway in cancer cells is associated with tumor occurrence, drug resistance and poor cancer prognosis (18). Gli1 activates the target genes downstream of the Shh pathway (19,20). It has been reported that Rab23 is associated with the Shh signaling pathway, but whether this correlation is positive or negative is still under debate.…”
Section: Discussionmentioning
confidence: 99%
“…Smo is a proto-oncogene and a key factor in the Hh signaling pathway (50), which activates the downstream transcription factor of the Gli family. The Gli family includes three molecules: Gli1, Gli2 and Gli3 (51). Gli1 is a potent transcriptional activator (10); Gli2 also acts as a transcriptional activator, whereas Gli3 mainly acts as a transcriptional repressor (52).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have demonstrated that the inhibitory effects of other natural products on pancreatic cancer are mediated by the inhibition of the Hh signaling pathway. An active component from Siegesbeckia glabrescens , germacranolide sesquiterpene lactone, inhibited Gli-mediated transcriptional activity in human pancreatic cancer AsPC-1 and PANC-1 cells, and decreased cancer cell proliferation and the expression of Gli-targeted genes (51). Deguelin, a natural compound from the flavonoid family, has been reported to suppress growth, migration and invasion, and to promote apoptosis in two pancreatic cancer cell lines, PANC-1 and BxPC-3, through suppression of the Hh signaling pathway (58).…”
Section: Discussionmentioning
confidence: 99%
“…It is well evidenced that oxidative stress induces NF-κB associated with MMP expression in the skin [9]. It was reported that S. glabrescens, which has been long used as an herbal medicine to treat inflammatory diseases, inhibited inducible nitric oxide synthase and cyclooxygenase-2 expression in lipopolysaccharide-activated RAW 264.7 macrophages [27]. Accordingly, it is conceivable that SGE prevents UVB through activation of the MAPK and NF-κB pathways.…”
Section: Effect Of Sge On Catalase and The Mapk/nf-κb Pathways In Vivomentioning
confidence: 99%